The Influence of Parental Educational Expectations on Children’s Higher Education Attainment: Re-estimation Based on Instrumental Variables - Lai, Ting; Liu, Fulan; Huang, Yiheng (Frontiers in Psychology, 2022)
Studies show that parental educational expectations (PEEs) serve as an intermediary variable between family background and children’s educational attainment. This paper re-examines the relationship between PEEs and children's higher educational attainment using data from the China Family Panel Studies (CFPS) 2010-2018. To address potential endogenous problems, we use the average College Enrolment Opportunity Index (CEOI) when the children were 10-12 years old as an instrumental variable for PEEs. The results revealed that: 1) PEEs had a direct impact on children's higher educational attainment independent of family background; 2) the magnitude of the effect was much larger (almost three times) than previous estimates after solving endogenous problems; 3) there was no significant gender difference in the effect of PEEs. In addition, we also found that PEEs had a greater impact on middle- and low-income families. Therefore, we argue that against the background of the “Double Reduction” policy, Chinese parents should change their conception of education and raise their expectations for their children and encourage them to strive for higher educational achievements.